Decreased value-sensitivity in schizophrenia. (January 2018) - Martinelli, Cristina; Rigoli, Francesco; Dolan, Ray J.; Shergill, Sukhwinder S.
Abstract: Pathophysiology in schizophrenia has been linked to aberrant incentive salience, namely the dysfunctional processing of value linked to abnormal dopaminergic activity. In line with this, recent studies showed impaired learning of value in schizophrenia. However, how value is used to guide behaviour independently from learning, as in risky choice, has rarely been examined in this disorder. We studied value-guided choice under risk in patients with schizophrenia and in controls using a task requiring a choice between a certain monetary reward, varying trial-by-trial, and a gamble offering an equal probability of getting double this certain amount or nothing. We observed that patients compared to controls exhibited reduced sensitivity to values, implying that their choices failed to flexibly adapt to the specific values on offer. Moreover, the degree of this value sensitivity inversely correlated with aberrant salience experience, suggesting that the inability to tune choice to value may be a key element of aberrant salience in the illness. Our results help clarify the cognitive mechanisms underlying improper attribution of value in schizophrenia and may thus inform cognitive interventions aimed at reinstating value sensitivity in patients. Highlights: How value processing guides behavior and decision-making in schizophrenia is unknown. We found reduced value sensitivity in patients with schizophrenia. In patients, reduced value sensitivity was linked with aberrant salience experience. Our results clarify value processing deficits and may inform cognitive interventions.